VD_FINDINFO HC / 2014 / 293 vom 21. Mai 2014 - VD Tribunal cantonal (2014)
FRAIS PROFESSIONNELS, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, VÉHICULE, PROHIBITION DE CONCURRENCE | 8 CC, 327a CO, 327b CO, 327c CO, 337 CO, 340 CO, 340a CO, 340c CO